Changes in the extracellular microenvironment and osteogenic responses of mesenchymal stem/stromal cells induced by in vitro direct electrical stimulation - Kasama Srirussamee; Ruikang Xue; Sahba Mobini; Nigel J. Cassidy; Sarah H. Cartmell (Journal of Tissue Engineering, 2021)
was influencing cell metabolic activity, whereas SPP1 mRNA expression was regulated by other faradic by-products. This study reveals how different electrical stimulation regime alters cellular regenerative responses and the roles of faradic by-products, that might be used as a physical tool to guide and control cell behaviour.
Keywords: Planarian Biology and Electrostimulation; Bone Tissue Engineering Materials; 3D Printing in Biomedical Research